Abstract 118: Ophtalmic‐ethmoidal dural arteriovenous fistula - Isaac E. Tello; Hector A. Montenegro (Stroke: Vascular and Interventional Neurology)
Introduction Ophtalmic dural arteriovenous fistula is not a common diagnosis. They usually present as subarachnoid hemorrhage, or parenquimatous hemorrhage as in our patient. Male, 46 years old, electric worker, right‐handed. Family: Diabetes mellitus, gastric cancer, COVID. Tobacco, Marihuana and alcohol positive. Presents SAH on October 2022 posterior to physical activity. Intense cephalea, nausea and vomit, anxiety, with no neurological deficit, and went to sleep. Two days after, he presents somnolence, altered verbal speech, and disorientation, and next day he presents seizure, then he goes to emergency. Physical examination: Normal. Neurological examination: Disorientation, confused and non‐fluent language, altered mental status. No other signs of focalization. No visual affectation. Methods Patient was evaluated at emergency room. CT: SAH and parenquimatous left frontal basal hemorrhage of 2x3.4cm. AngioCT: a dilated orbito frontal vein, and a venous aneurysm at the anterior third of the superior sagittal sinus. Fronto basal fistula was suspected. Angiography was performed, and it was found right fronto‐basal arteriovenous fistula Borden III, Cognard IV. Comunication between righ ophthalmic artery to superior sagittal sinus. Patient was delivered home three days after the event. When patient had recovered clinically, we performed embolization. Results We performed doble access, femoral artery and braquial vein. It was not possible to achieve to the fistula through vein system. We catheterized ophthalmic artery, and did embolization through it, with a successful result, and with no ophthalmic symptoms after embolization. Conclusion Dural arteriovenous fistulas are shunts found from dural vessels. This type of fistulas ophthalmic‐ethmoidal are rare. We performed angiography which is the know gold standard for diagnosis, and we tried to do a combined access which was not possible, so we performed simple embolization through ophthalmic artery. This approach it is performed and it has been reported as an effective and safe treatment.